COMPARISON OF GENERAL TECHNICAL PARAMETERS, WORKABILITY AND FIRE PROTECTION OF ROLLED PROFILES VS. RHS STEEL FRAMES OF 3D-VOLUMETRIC MODULES (Collection of scientific works «Modern structures of metal and wood», 2024)
Prefabricated  volumetric  modules  with  steel  frame  have  recently  become  a segmentation trend for real estate, commercial multi-storey housing and office buildings projects. The obvious benefits of reducing construction time, number of site activities and related overheads as well as better quality control system compare to on-site production, 3D volumetric construction still associated with significant risks related to relatively high construction cost, potential logistics issues and lack of proven point of reference and frameworks (so-called “best practices”). Despite the fact that prefabricated modular construction known for almost a century, researches on design problems and limitations of practical implementation of volumetric modules today are still fragmentary and insufficient.  Numbers  of  researches  focused  on  the  improving  of  steel  frames  of  three-dimensional volumetric modules and their performance-based optimization, related either to the design of effective joints  (e.g.  self-clamp  joints)  or  study  the  problems  of  spatial  stability  of  multi-storey  modular buildings, considering the own weight of load-bearing structures as a criterion for design efficiency. The  case  study  illustrates  that  estimation  of  design  efficiency  of  prefabricated  volumetric modules with steel frames, besides the factors of durability and sustainability of the structure included required level of fire resistance, and the criteria of the economic efficiency of design also includes the  fire protected surface area of the steel elements.